The value of the NMP22 test for superficial bladder cancer diagnosis and follow-up - Doğan, Caner (Turk J Urol, 2013)
OBJECTIVE: In this study, we investigated the efficacy of nuclear matrix protein 22 (NMP22) in the diagnosis and surveillance of bladder cancer. MATERIAL AND METHODS: Patients with hematuria or who applied for cystoscopic control of proven bladder cancer were prospectively enrolled in this study. Routine cytologic examination and NMP22 test were performed on the voided urine sample obtained before the cystoscopy. The patients who had been diagnosed with bladder cancer were categorized according to stage, grade, number, size of the tumor and risk of the disease. Then the diagnostic performance of the NMP22 and the cytology test, alone or in combination, were evaluated separately using ROC curves in the diagnosis and surveillance groups. RESULTS: A total of 87 patients (87/136) were investigated because of hematuria. The sensitivity, specificity, positive and, negative predictive values, and positive likelihood ratio (LR+) of the NMP22 test were 70, 80, 68, 81, and 3.42%, respectively. While, the sensitivity, specificity, positive and, negative predictive values, and positive likelihood ratio (LR+) of the cytology examination were 27, 96, 82, 68, and 7.36%, respectively. There were 49 patients in the bladder cancer group. The sensitivity, specificity, positive, and negative predictive values and positive likelihood ratio (LR+) of the NMP22 test in these patients were 33, 76, 31, 78 and 1.37%, respectively. The sensitivity, specificity, positive and, negative predictive values, and positive likelihood ratio (LR+) of the cytology examination were 25%, 97%, 75%, 80% and 9.25, respectively. CONCLUSION: NMP22 test can be used as an adjunctive tool for the detection of bladder cancer, but its diagnostic performance is limited in surveillance when used alone or in combination with a cytology examination.